Transcriptome-Wide Study of mRNAs and lncRNAs Modified by m6A RNA Methylation in the Longissimus Dorsi Muscle Development of Cattle-Yak - Chun Huang; Rongfeng Dai; Guangyao Meng; Renqing Dingkao; Xingdong Wang; Wenwen Ren; Xiaoming Ma; Xiaoyun Wu; Min Chu; Yongfu La; Pengjia Bao; Xian Guo; et al. (Cells, 2022)
Cattle-yak is a hybrid F1 generation of cattle and yak, which has a history of more than 3000 years and has shown better production performance and higher economic benefits than those of yaks. However, up to now, there has been no study on the transcriptome-wide m6A methylation profile of bovine skeletal muscle and its potential biological function during muscle development. Here, we observed significant changes in the expression levels of muscle-related marker genes and methylation-related enzymes during the development of cattle-yak, and the overall m6A content in the Longissimus dorsi muscle of 18-month-old cattle-yak decreased significantly. A total of 36,602 peaks, 11,223 genes and 8388 lncRNAs were identified in the two groups, including 2989 differential peaks (427 up-regulated peaks and 2562 down-regulated peaks), 1457 differentially expressed genes (833 up-regulated genes and 624 down-regulated genes) and 857 differentially expressed lncRNAs (293 up-regulated lncRNAs and 564 down-regulated lncRNAs). GO and KEGG analysis revealed that they were significantly enriched in some muscle-related pathways (Wnt signaling pathway and MAPK signaling pathway) and high-altitude adaptation-related pathway (HIF-1 signaling pathway). Moreover, m6A abundance was positively correlated with gene expression levels, while it was negatively correlated with lncRNA expression levels. This indicates that m6A modification played an important role in the Longissimus dorsi muscle development of cattle-yak; however, the regulation mechanism of m6A-modified mRNA and lncRNA may be different. This study was the first report of transcriptome-wide m6A-modified mRNAs and lncRNAs atlas in the Longissimus dorsi muscle development of cattle-yak, one which will provide new perspectives for genetic improvement in bovines.